PARP inhibitors as therapy for small cell lung carcinoma: A systematic review and meta-analysis of clinical trials - Samuel Pratama; Lowilius Wiyono; Martien Silviandy Setiawan; Brigitta Cindy Lauren (Cancer Treatment and Research Communications)
Background: Small Cell Lung Cancer (SCLC) is a neuroendocrine carcinoma characterized by aggressive behavior and poor prognosis with limited treatment options. Poly ADP-Ribose Polymerase inhibitors (PARPi) are novel anti-cancer agents that induce DNA damages and cause cell death in tumor cells with impaired DNA repair, known as the synthetic lethality concept. This study aimed to analyze the efficacy and safety of PARPi for patients with SCLC from available clinical trial data. Methods: Studies reporting efficacy and safety of PARPi therapy for SCLC patients were searched across five databases with predetermined eligibility criteria in accordance with the PRISMA statement. Critical appraisal was done using suitable tools, outcomes were extracted, and analyzed. Results: Five randomized controlled clinical trials with 451 interventional patients and 308 control patients with SCLC were included. The analysis showed increased Progression-Free Survival (PFS) (RR 0.92 (95 %CI 0.84–1.00; p=0.05)) and Objective Response Rate (ORR) (RR 1.27 (95 %CI 1.07–1.50; p=0.007)), no significant difference in Overall Survival (OS) (RR 1.03 (95 %CI 0.92–1.15; p=0.60)), and an increased risk for serious Treatment Emergent Adverse Events (TEAEs) (RR 1.13 (95 %CI 0.95–1.35; p=0.16)) in PARPi-receiving SCLC patients. Amongst the hematologic toxicities, sub-analysis showed that thrombocytopenia had the highest risk, followed by neutropenia, anemia, leukopenia, and lymphopenia. Conclusion: The addition of PARPi in the chemotherapy regimen for patients with SCLC results in increased PFS and ORR, with no difference in OS and an increased risk of TEAEs. Further and larger clinical studies are needed to validate the efficacy and safety of PARPi therapy for SCLC patients.